PENGENALAN PEMANFAATAN TEKNOLOGI INTERNET OF THINGS (IoT) BAGI SISWA SISWI SMA NEGERI 1 AIR JOMAN - Yusda, Riki Andri; Sahren, Sahren; Sholat, Junaidi; Aditya, Bima; Rafly, Muhammad (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: The internet has transformed not only data exchange through standard devices such as PCs, laptops, or smartphones, but also shifted to various tools in our surroundings. This concept is known as the Internet of Things (IoT). IoT is defined as a system consisting of networks of sensors, actuators, and smart objects aimed at connecting all items, including everyday objects and those used in industry, making them intelligent, programmable, and capable of interacting with humans. IoT has been widely implemented in various sectors, such as smart cities, innovative healthcare, smart agriculture, smart education, and others. Introducing IoT at an early age, particularly in high schools, is essential, with the hope of fostering students' interest in this field. In this community service initiative, IoT technology was introduced at SMA Negeri 1 Air Joman, by delivering materials on IoT technology and its applications.Keywords: high school, IoT. Abstrak: Penggunaan internet telah mengalami transformasi, tidak hanya untuk pertukaran data melalui perangkat umum seperti PC, laptop, atau smartphone, tetapi juga beralih ke berbagai alat yang ada di sekitar kita. Konsep ini dikenal sebagai Internet of Things (IoT). IoT didefinisikan sebagai sistem yang terdiri dari jaringan sensor, aktuator, dan objek pintar yang bertujuan untuk menghubungkan semua barang, termasuk objek sehari-hari dan yang digunakan dalam industri, sehingga menjadikannya pintar, dapat diprogram, dan mampu berinteraksi dengan manusia. IoT telah banyak diterapkan di berbagai sektor, seperti kota pintar, kesehatan pintar, pertanian pintar, pendidikan pintar, dan bidang lainnya. Pengenalan IoT perlu dilakukan sejak dini, terutama di sekolah menengah atas, dengan harapan dapat meningkatkan minat siswa untuk mendalami bidang ini. Dalam pengabdian masyarakat ini, dilakukan pengenalan teknologi IoT di SMA Negeri 1 Air Joman, melalui penyampaian materi tentang teknologi IoT dan aplikasinya.Kata kunci: IoT, SMA.